Dosa-dosa besar / Imam Adz-Dzahabi; penerjemah, Abu Zufar Imtihan Asy-Syafi'i; editor, Abu Fatiah Al-Adnani, Qodsi Ridlwanullah - ADZ-DZAHABI , Imam; Abu Zufar Imtihan Asy-Syafi'i; Abu Fatiah Al-Adnani; Qodsi Ridlwanullah (Pustaka Arafah, 2016)
418 hlm. ; 24 cm.